Decriminalization of abortion: a muted cry - Rosário, Luana Paixão Dantas do; Braga, Bruna Mascarenhas (Revista Hipótese, 2016)
This paper aims to determine how the normative discourse criminalizing abortion, patriarchal matrix, interdicts and subjugates women. Used Foucault setting for speech and Bakthin for language subjects. It is considered the speech as a space of struggle. Shows the difficulty of normative discourse with female sexuality and, therefore, the sexual rights of women. It points out how the understanding of sexual rights has been reduced to reproductive rights. It is proposed that the emancipatory discourse struggles of women produce cracks in the dominant normativity. From a phenomenological view, fixed in methodological pluralism, will combine the hermeneutical comprehensive methodological approach to the method of interpretation of French origin discourse analysis. The technique will be the literature.
Keywords: Abortion; Genre; Sexual Rights; Speech; Normativity